2015
DOI: 10.12968/ijpn.2015.21.9.453
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of hospice inpatient nurses in supporting children before the death of a parent

Abstract: Multiple factors influencing provision of support emerged. Formal training and readily available resources would support hospice nurses working with children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(80 citation statements)
references
References 13 publications
2
78
0
Order By: Relevance
“…Professions included specialist palliative care nurses, 810,1922,27,49 oncology nurses, 7,21,27,50,51 general nurses, 7,26,52 community nurses, 8,9,19,22,26,49 physicians (doctors) 22,51 ( n = 22), physical therapists ( n = 6), 22 psychologists ( n = 2) 22 and social workers ( n = 5). 19 Fields of work were inpatient oncology, 7,21,27,28,49,51 haematology, 7,51 neurology, 7,51 oncological gynaecology, 51 palliative care in hospices, 10,19,20,22 in the community, 8,9,19,26,49 for example, in nursing homes 10,22 and in patients’ homes. 8,9,10,19,22,26,49 One study does not state the setting.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Professions included specialist palliative care nurses, 810,1922,27,49 oncology nurses, 7,21,27,50,51 general nurses, 7,26,52 community nurses, 8,9,19,22,26,49 physicians (doctors) 22,51 ( n = 22), physical therapists ( n = 6), 22 psychologists ( n = 2) 22 and social workers ( n = 5). 19 Fields of work were inpatient oncology, 7,21,27,28,49,51 haematology, 7,51 neurology, 7,51 oncological gynaecology, 51 palliative care in hospices, 10,19,20,22 in the community, 8,9,19,26,49 for example, in nursing homes 10,22 and in patients’ homes. 8,9,10,19,22,26,49 One study does not state the setting.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,10,49,50,52 In five studies, they reported experiences of supporting children directly, rather than connecting with children through their parents. 7,8,19,20,22 Although supporting children following the death of a parent was mentioned in two studies, 10,22 only one focussed specifically on health and social care professionals’ experiences of supporting children when their parent was dying, and following parental death. 22…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations